Virtual Screening Natural Compounds from Plants as Inhibitor of Estrogen Receptor Alpha I (ESR1) - Andi Trihadi Kusuma; Daryono Hadi (Indonesian Journal of Pharmaceutical Science and Technology, 2019)
Flavanoid is one of the chemical compounds found in plants. Isoflavones (1.2-diarylpropane) are the largest group in the flavanoid that can be used to study the anticancer activity. 2IOK is one oftarget inhibitors which is obtainedfrom natural product compounds.The purpose of the research is to design new compounds have anti-cancer activity, especially for breast cancer based on the evaluation of the affinity of the compound against Estrogen Receptor Alpha (ESR1) usingthecomputational method. The parent compound is the test structure of isoflavones which has been reported to have anticancer activity, particularly for breast cancer. Based on the results of the validation method of docking with several combinations, the best method found was Triangle matcher-Affinity dG with anRMSDof 1.0452. Furthermore, this model providesROC graph value of  0.863. Therefore, the method was used  to screen compounds  in the UI database. Three compounds wereobtained from the process, which are potentially active against Estrogen Receptor Alpha (ESR1), namely C00010051, C00026048, C00025295. The MD simulations of protein-ligand complexes indicated exchanges process, namely the absence of  interaction between the ligand with the Phe404, insteadofthe ligand formed  hydrogen bonding with Glu353. Meanwhile, the C00025295 compound formed hydrogen bonding with the Leu346 residue.Keywords: virtual screening, molecular docking, molecular dynamic, ESR1